Моделирование распространения примеси от придонных источников в северо-западной части Черного моря - Алексеев, Д.В.; Иванча, Е.В.; Фомин, В.В.; Черкесов, Л.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The admixture transport from sources located on the bottom of the Black-Sea north-western shelf in the places of exploited gas fields is studied by using a σ-coordinate numerical model. The fields of currents are formed due to the effect of seasonal winds and the joint action of a seasonal wind and the wind related to the cyclonic formation passage. Transient currents caused by a moving atmospheric disturbance influence determinatively the admixture spreading. The estimations of the magnitude and direction of displacements of the pollution areas on different horizons in the presence and in the absence of a cyclone are given.